Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the problem, we need to utilize the sum and product of the roots of the given polynomial [tex]\(2x^2 - 4x + 5\)[/tex]. Here, [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] are the zeroes of the polynomial.
Sum and Product of roots:
For a polynomial [tex]\(ax^2 + bx + c = 0\)[/tex]:
- The sum of the roots, [tex]\(\alpha + \beta\)[/tex], is given by [tex]\(-\frac{b}{a}\)[/tex].
- The product of the roots, [tex]\(\alpha \beta\)[/tex], is given by [tex]\(\frac{c}{a}\)[/tex].
Given the polynomial [tex]\(2x^2 - 4x + 5\)[/tex]:
- [tex]\(a = 2\)[/tex], [tex]\(b = -4\)[/tex], and [tex]\(c = 5\)[/tex].
Step-by-step solutions:
### Part (a): [tex]\(\alpha^2 + \beta^2\)[/tex]
We use the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha\beta \][/tex]
1. Calculate the sum of the roots:
[tex]\[ \alpha + \beta = -\frac{b}{a} = -\frac{-4}{2} = 2 \][/tex]
2. Calculate the product of the roots:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{5}{2} \][/tex]
3. Substitute the values into the identity:
[tex]\[ \alpha^2 + \beta^2 = (2)^2 - 2 \left(\frac{5}{2}\right) \][/tex]
[tex]\[ \alpha^2 + \beta^2 = 4 - 2 \times \frac{5}{2} \][/tex]
[tex]\[ \alpha^2 + \beta^2 = 4 - 5 \][/tex]
[tex]\[ \alpha^2 + \beta^2 = -1 \][/tex]
Thus, [tex]\(\alpha^2 + \beta^2 = -1\)[/tex].
### Part (b): [tex]\(\frac{1}{\alpha} + \frac{1}{\beta}\)[/tex]
We use the identity:
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{\alpha + \beta}{\alpha \beta} \][/tex]
1. Substitute the values of the sum and product of the roots:
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{2}{\frac{5}{2}} \][/tex]
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = 2 \times \frac{2}{5} \][/tex]
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{4}{5} \][/tex]
Thus, [tex]\(\frac{1}{\alpha} + \frac{1}{\beta} = 0.8\)[/tex].
### Part (c): [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2}\)[/tex]
We use the identity:
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{\alpha^2 + \beta^2}{(\alpha \beta)^2} \][/tex]
1. Substitute the values of [tex]\(\alpha^2 + \beta^2\)[/tex] and [tex]\((\alpha \beta)^2\)[/tex]:
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{-1}{\left(\frac{5}{2}\right)^2} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{-1}{\frac{25}{4}} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = -1 \times \frac{4}{25} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = -\frac{4}{25} \][/tex]
Thus, [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2} = -0.16\)[/tex].
Final Results:
a) [tex]\(\alpha^2 + \beta^2 = -1\)[/tex]
b) [tex]\(\frac{1}{\alpha} + \frac{1}{\beta} = 0.8\)[/tex]
c) [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2} = -0.16\)[/tex]
Sum and Product of roots:
For a polynomial [tex]\(ax^2 + bx + c = 0\)[/tex]:
- The sum of the roots, [tex]\(\alpha + \beta\)[/tex], is given by [tex]\(-\frac{b}{a}\)[/tex].
- The product of the roots, [tex]\(\alpha \beta\)[/tex], is given by [tex]\(\frac{c}{a}\)[/tex].
Given the polynomial [tex]\(2x^2 - 4x + 5\)[/tex]:
- [tex]\(a = 2\)[/tex], [tex]\(b = -4\)[/tex], and [tex]\(c = 5\)[/tex].
Step-by-step solutions:
### Part (a): [tex]\(\alpha^2 + \beta^2\)[/tex]
We use the identity:
[tex]\[ \alpha^2 + \beta^2 = (\alpha + \beta)^2 - 2\alpha\beta \][/tex]
1. Calculate the sum of the roots:
[tex]\[ \alpha + \beta = -\frac{b}{a} = -\frac{-4}{2} = 2 \][/tex]
2. Calculate the product of the roots:
[tex]\[ \alpha \beta = \frac{c}{a} = \frac{5}{2} \][/tex]
3. Substitute the values into the identity:
[tex]\[ \alpha^2 + \beta^2 = (2)^2 - 2 \left(\frac{5}{2}\right) \][/tex]
[tex]\[ \alpha^2 + \beta^2 = 4 - 2 \times \frac{5}{2} \][/tex]
[tex]\[ \alpha^2 + \beta^2 = 4 - 5 \][/tex]
[tex]\[ \alpha^2 + \beta^2 = -1 \][/tex]
Thus, [tex]\(\alpha^2 + \beta^2 = -1\)[/tex].
### Part (b): [tex]\(\frac{1}{\alpha} + \frac{1}{\beta}\)[/tex]
We use the identity:
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{\alpha + \beta}{\alpha \beta} \][/tex]
1. Substitute the values of the sum and product of the roots:
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{2}{\frac{5}{2}} \][/tex]
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = 2 \times \frac{2}{5} \][/tex]
[tex]\[ \frac{1}{\alpha} + \frac{1}{\beta} = \frac{4}{5} \][/tex]
Thus, [tex]\(\frac{1}{\alpha} + \frac{1}{\beta} = 0.8\)[/tex].
### Part (c): [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2}\)[/tex]
We use the identity:
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{\alpha^2 + \beta^2}{(\alpha \beta)^2} \][/tex]
1. Substitute the values of [tex]\(\alpha^2 + \beta^2\)[/tex] and [tex]\((\alpha \beta)^2\)[/tex]:
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{-1}{\left(\frac{5}{2}\right)^2} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = \frac{-1}{\frac{25}{4}} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = -1 \times \frac{4}{25} \][/tex]
[tex]\[ \frac{1}{\alpha^2} + \frac{1}{\beta^2} = -\frac{4}{25} \][/tex]
Thus, [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2} = -0.16\)[/tex].
Final Results:
a) [tex]\(\alpha^2 + \beta^2 = -1\)[/tex]
b) [tex]\(\frac{1}{\alpha} + \frac{1}{\beta} = 0.8\)[/tex]
c) [tex]\(\frac{1}{\alpha^2} + \frac{1}{\beta^2} = -0.16\)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.